Calf muscle stretching is ineffective in increasing ankle range of motion or reducing plantar pressures in people with diabetes and ankle equinus: A randomised controlled trial. (October 2019) - Searle, Angela; Spink, Martin J.; Oldmeadow, Christopher; Chiu, Simon; Chuter, Vivienne H.
Abstract: Background: Limited ankle dorsiflexion, or equinus, is associated with elevated plantar pressures, which have been implicated in the development and non-healing of foot ulcer. A stretching intervention may increase ankle dorsiflexion and reduce plantar pressures in people with diabetes. Methods: Two arm parallel randomised controlled trial from September 2016 to October 2017. Adults with diabetes and ankle equinus (≤5° dorsiflexion) were randomly allocated to receive an 8 week static calf stretching intervention or continue with their normal activities. Primary outcome measures were change in weight bearing and non-weight bearing ankle dorsiflexion and forefoot peak plantar pressure. Secondary outcome measures were forefoot pressure time integrals and adherence to the stretching intervention. Findings: 68 adults (mean (standard deviation) age and diabetes duration 67.4 (10.9) years and 14.0 (10.8) years, 64.7% male) were randomised to stretch (n = 34) or usual activity (n = 34). At follow up, no significant differences were seen between groups (adjusted mean difference) for non-weight (+1.3°, 95% CI:−0.3 to 2.9, p = 0.101) and weight bearing ankle dorsiflexion (+0.5°, 95% CI:−2.6 to 3.6, p = 0.743) or forefoot in-shoe (+1.5 kPa, 95% CI:−10.0 to 12.9, p = 0.803) or barefoot peak pressures (−19.1 kPa, 95% CI:−96.4 to 58.1, p = 0.628). Seven of the intervention group and two of the control group were lost to follow up. Interpretation: Our data failed to show a statistically significant or clinically meaningful effect of static calf muscle stretching on ankle range of motion, or plantar pressures, in people with diabetes and ankle equinus. Highlights: Ankle equinus is associated with increased plantar pressure in people with diabetes. Adults with diabetes and ankle equinus undertook 8 weeks of static calf stretching. No significant increase in ankle dorsiflexion was seen following the intervention. Additionally no significant reduction in plantar pressures was noted.